Mountain Tourism Development through the Sustainable Livelihood Approach: A Case Study of Dhorpatan Valley, Nepal (Journal of Tourism and Himalayan Adventures, 2020)
Geography of Nepal has largely caused serious constraints to physical development works in mountain regions and consequently has lagged behind those of lowland areas. Topography challenges available livelihood options, and thereby these areas are often defined by higher poverty rates, lower education levels, limited access to services and increasing out-migration. Therefore, it is essential to identify the baseline assets available for mountain communities in order for them to develop. A tool for assessing livelihood assets is the Sustainable Livelihoods Approach (SLA) which evaluates forms of natural, human, physical, financial, social, cultural and political capital. Tourism can be supported by, as well as potentially augment, these various forms of community assets, but conversely weaknesses in these assets will form a barrier to development. This paper uses the SLA to examine the Dhorpatan valley, a high altitude valley in a mountainous region of western Nepal. Suggestions for future tourism development are identified along with potential challenges.